Post-socialist moral economies of consumption as socially embedded sites of moral tension. (May 2020) - Swader, Christopher S.; Ross, Sandy
Consumption was one of the spheres of everyday life shaken and remoulded by the collapse of socialist regimes at the end of the 20th century. Especially in times of rapid change, a moral economies lens is a fruitful means to understand the contentious moral landscape and moral tensions that pervade consumption behaviour, norms and discourse. Important areas of consideration in post-socialist societies in this field include links between ideology and consumption; transformations of material culture, especially luxury culture; the retraditionalisation and polarisation of gender; and intergenerational and social class divisions. Theoretically, we stress the importance of multiple levels of analysis and address both the empirical and critical dimensions of 'moral economy'. In particular, this recognises the importance of the Zelizerian relational approach while cautioning against the hostile worlds rhetorical frame. It is through the simultaneous critical and empirical approaches of Polanyi and Thompson that an important analytical focus for post-socialist moral economies of consumption and beyond – moral tensions – is made plain.